2012
DOI: 10.1063/1.4730964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proton bombardment on InAs dots and wetting layer in laser structures

Abstract: The effect of proton bombardment on carrier lifetime and photoluminescence of InAs quantum dots was measured. Optical absorption and transmission electron microscopy show the dots retain their integrity under bombardment. A decrease in ground state photoluminescence with increasing dose is not explained by the decrease in dot carrier lifetime alone, but also by bombardment-induced non-radiative recombination in the wetting layer, which reduces the dot electron population at fixed excitation. To exploit the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…23. The absorption peak was not shifted by bombardment, and transmission electron microscopy showed the integrity of the dots was retained.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…23. The absorption peak was not shifted by bombardment, and transmission electron microscopy showed the integrity of the dots was retained.…”
mentioning
confidence: 86%
“…Time-resolved luminescence showed a factor ten faster decay at the transition energy, and analysis in Ref. 23 shows that defects are also introduced into the wetting layer, so at low temperatures, carriers can also be lost by tunnelling to nearby defect states. 24 Mode-locking was observed in these devices with pulse widths reducing by a factor 29 from 8.4 ps at 250 K to 290 fs at 20 K, and this correlates with the temperature dependence of threshold of the same structures, as shown in Fig.…”
mentioning
confidence: 99%
“…In the saturable absorber, the main mechanism by which carriers are lost from the dot at low temperatures is emission to the wetting layer [10] and this becomes very slow below about 225 K [11]. We have therefore bombarded the absorber sections with protons, with energy of 250 keV and dose of 1 × 10 12 cm −2 , to introduce nonradiative recombination centers and increase the recombination rate to reduce the recovery time.…”
Section: Device Structures and Experimental Detailsmentioning
confidence: 99%
“…A few research groups have reported encouraging results of QD lasers showing enhanced resistance to radiation damage [1][2][3], but complete understanding of physical mechanisms leading to this enhancement is still lacking. Also, it is well known that point defects induced by proton irradiation behave as nonradiative recombination centers (NRCs), but the role that NRCs play in reliability and degradation mechanisms in QD lasers is not well understood.…”
Section: Introductionmentioning
confidence: 96%